Davison, Stan (London, 2013)
2013 "Davison, Stan", 2013, HistoryTalk On leaving the army at the age of twenty Stan did an electricians course in Surrey for six months. He immediately joined a printing firm in central London called Novellos found for him through the Hendon ETU (Electrical Trades Union). Describes the period of the Cold War in the 1950s and the role of the CIA and Catholic Action. He moved to BEA (British European Airways) at Northolt for ten years (1949- 59) followed by ten years working full- time for the CPGB in which did a variety of organisational and agitational tasks with an office in Southall and then ten years on London Transport until retirement in 1989. Here he worked as an electrician and was a member of the Craft Alliance in LT garages working on Routemaster buses.